2018
DOI: 10.3991/ijoe.v14i12.8630
|View full text |Cite
|
Sign up to set email alerts
|

Towards Simulation Aided Online Teaching: Material Design for Applied Fluid Mechanics

Abstract: Learning is shifting from synchronous in-class settings to asynchronous online platforms in an attempt to make education accessible to wider audience. However, certain vital components of engineering education, such as laboratory work and hands-on practices, are harder to conduct online. Understanding how technology can help offering such components online can impact the quality of online education a great deal. The goal of this study is to improve the effectiveness of online courses in engineering. Particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A group of 21 articles reported on students' control over the pace of their progression within the modules, choosing among the module components to interact with (e.g. Altuger-Genc et al, 2018;Henson et al, 2002) or freedom to skip parts (e.g. Pierre et al, 2009).…”
Section: Modular Course Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of 21 articles reported on students' control over the pace of their progression within the modules, choosing among the module components to interact with (e.g. Altuger-Genc et al, 2018;Henson et al, 2002) or freedom to skip parts (e.g. Pierre et al, 2009).…”
Section: Modular Course Designmentioning
confidence: 99%
“…Most (weekly) in-class time, intended to cover the theoretical course content. As indicated by Altuger-Genc et al (2018), modules: "support the in-class learning as well as to provide students a hands-on and visual animation they can employ to understand the theory better." All articles reported that the students were expected to use the modules before or after the face-to-face sessions.…”
Section: Modular Course Designmentioning
confidence: 99%